Up-skilling associate clinicians in Malawi in emergency obstetric, neonatal care and clinical leadership: the ETATMBA cluster randomised controlled trial. Issue 1 (7th July 2016) - Ellard, David R; Chimwaza, Wanangwa; Davies, David; Simkiss, Doug; Kamwendo, Francis; Mhango, Chisale; Quenby, Siobhan; Kandala, Ngianga-bakwin; O'Hare, Joseph Paul
Abstract : Background: The ETATMBA (Enhancing Training And Technology for Mothers and Babies in Africa) project-trained associate clinicians (ACs/clinical officers) as advanced clinical leaders in emergency obstetric and neonatal care. This trial aimed to evaluate the impact of training on obstetric health outcomes in Malawi. Method: A cluster randomised controlled trial with 14 districts of Malawi (8 intervention, 6 control) as units of randomisation. Intervention districts housed the 46 ACs who received the training programme. The primary outcome was district (health facility-based) perinatal mortality rates. Secondary outcomes included maternal mortality ratios, neonatal mortality rate, obstetric and birth variables. The study period was 2011–2013. Mortality rates/ratios were examined using an interrupted time series (ITS) to identify trends over time. Results: The ITS reveals an improving trend in perinatal mortality across both groups, but better in the control group (intervention, effect −3.58, SE 2.65, CI (−9.85 to 2.69), p=0.20; control, effect −17.79, SE 6.83, CI (−33.95 to −1.64), p=0.03). Maternal mortality ratios are seen to have improved in intervention districts while worsening in the control districts (intervention, effect −38.11, SE 50.30, CI (−157.06 to 80.84), p=0.47; control, effect 11.55, SE 87.72, CI (−195.87 to 218.98), p=0.90). There was a 31% drop in neonatal mortality rate in intervention districts while in control districts, the rate rises by 2%. There are no significant differences in the other secondary outcomes. Conclusions: This is one of the first randomised studies looking at the effect of structured training on health outcomes in this setting. Notwithstanding a number of limitations, this study suggests that up-skilling this cadre is possible, and could impact positively on health outcomes. Trial registration number: ISRCTN63294155; Results.